(untitled) (Journal of Parents and Teachers, 2017)
The students of 3º Grade of Primary Education from Universidad Pontificia Comillas have a mission: to collaborate with the Fundación del Valle in the formation of 60 teachers on the multiplication in Guatemala. For this, we have made manipulative materials, dynamics and games based on a theoretical foundation. This project has been very enriching at a professional and personal level, and although we were the artisans, the protagonists were always the children from Guatemala.